Enhancing clinical and public health interpretation of accelerometer-assessed physical activity with age-referenced values based on UK Biobank data - Alex V. Rowlands; Andrew P. Kingsnorth; Bjørge H. Hansen; Stuart J. Fairclough; Lynne M. Boddy; Benjamin D. Maylor; Henrik R. Eckmann; Borja del Pozo Cruz; Nathan P. Dawkins; Cameron Razieh; Kamlesh Khunti; Francesco Zaccardi; et al. (Journal of Sport and Health Science)
Background: Higher accelerometer-assessed volume and intensity of physical activity (PA) have been associated with a longer life expectancy but can be difficult to translate into recommended doses of PA. We aimed to: (a) improve interpretability by producing UK Biobank age-referenced centiles for PA volume and intensity; (b) inform public-health messaging by examining how adding recommended quantities of moderate and vigorous PA affect PA volume and intensity. Methods: 92,480 UK Biobank participants aged 43–80 years with wrist-worn accelerometer data were included. Average acceleration and intensity gradient were derived as proxies for PA volume and intensity. We generated sex-specific centile curves using Generalized Additive Models for Location Scale and Shape (GAMLSS) and modeled the effect of adding moderate (walking) or vigorous (running) activity on the combined change in the volume and intensity centiles (change in PA profile). Results: In men, volume was lower as age increased while intensity was lower after age 55; in women, both volume and intensity were lower as age increased. Adding 150 min of moderate PA weekly (5 × 30 min walking) increased the PA profile by 4 percentage points. Defining moderate PA as brisk walking approximately doubled the increase (9 percentage points) while 75 min of vigorous PA weekly (5 × 15 min running) trebled the increase (13 percentage points). Conclusion: These UK Biobank reference centiles provide a benchmark for interpretation of accelerometer data. Application of our translational methods demonstrate that meeting PA guidelines through shorter duration vigorous activity is more beneficial to the PA profile (volume and intensity) than longer duration moderate activity.